2006
DOI: 10.1111/j.1479-6988.2006.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive systematic review of evidence on the effectiveness and appropriateness of undergraduate nursing curricula

Abstract: Objectives  The objective of this review was to appraise and synthesise the best available evidence on the effectiveness and appropriateness of undergraduate nursing curricula. Inclusion criteria  This review considered research papers that addressed the effectiveness and appropriateness of undergraduate nursing curricula. Studies of higher evidence levels were given priority over lower-evidence studies. Participants of interest were undergraduate nursing students, nursing staff and healthcare consumers. Nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Few studies indicated that a teacher in the health professions must be equally skilled as both a classroom teacher and a clinical preceptor or mentor (an individual who guides learning for one or more students in the clinical setting). Rather, the descriptive literature supports the importance of the preceptor/mentor role as complementary to the role of the academic educator [30]. The role of the preceptor has been particularly well explored, and studies confirm the need for preceptors to develop skills in clinical teaching, identification of student learning needs, assessment of student learning, and prioritizing and time management [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies indicated that a teacher in the health professions must be equally skilled as both a classroom teacher and a clinical preceptor or mentor (an individual who guides learning for one or more students in the clinical setting). Rather, the descriptive literature supports the importance of the preceptor/mentor role as complementary to the role of the academic educator [30]. The role of the preceptor has been particularly well explored, and studies confirm the need for preceptors to develop skills in clinical teaching, identification of student learning needs, assessment of student learning, and prioritizing and time management [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Jayasekara et al (2006) offer a systematic review of comparative studies that attempt to distinguish between the effectiveness of various approaches to curriculum design in nursing. These authors note the paucity of studies that address overall effectiveness of any approach.…”
Section: Discussionmentioning
confidence: 99%
“…There are little data to offer a valid base to estimate incremental costs (or savings) or revenue requirements. This lack of high-quality comparative studies with meaningful outcome measures allows no definitive conclusion regarding the general effectiveness of undergraduate curricula [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our current literature search retrieved only 8 publications addressing cost-effectiveness and issues of medical education with the search terms (“cost effectiveness*”[TI] OR “cost benefit*”[TI]) AND analy* AND (“medical education” OR student* OR undergraduat*). Only four of these referred to the cost effectiveness or cost benefit of medical training itself [ 4 , 6 – 8 ]. The costs within medical education programs seem worryingly high with – at least in part – little student satisfaction even in issues of perceived strong relevance (as shown for a course teaching on terminal care [ 7 ]).…”
Section: Introductionmentioning
confidence: 99%